Determinant Analysis of MSE Owners' Interest in Islamic Banking Financing in Kenagarian Kinari: A Confirmatory Factor Analysis Approach - Adif, Riandy Mardhika; Andespa, Roni; Naldi, Ool (Institut Agama Islam Negeri Kendari, 2024)
This study examines the factors influencing Micro and Small Enterprise (MSE) owners' interest in accessing Islamic banking financing in Kenagarian Kinari. Using a quantitative approach and Confirmatory Factor Analysis (CFA), the research involved 89 MSE owners who had not yet accessed Islamic bank financing. The analysis identified ten key factors influencing MSE owners' interest: social factors (27.393%), location (8.879%), marketing mix (7.033%), promotion (5.868%), cultural (5.018%), product (4.473%), procedural (3.930%), personal (3.490%), belief (3.232%), and psychological factors (3.053%). Notably, social factors, encompassing group recommendations, family encouragement, and work environment influence, emerged as the most dominant determinant with the highest loading factor. This research provides significant contributions to developing Islamic banking strategies in reaching the MSE segment and enhancing Islamic financial inclusion at the village level.